2006
DOI: 10.1021/jp065245y
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Chemistry of Butanol and Decanol with Sulfuric Acid:  Implications for Secondary Organic Aerosol Formation

Abstract: Recent environmental chamber studies suggest that acid-catalyzed reactions between alcohols and aldehydes in the condensed phase lead to the formation of hemiacetals and acetals, enhancing secondary organic aerosol (SOA) growth. We report measurements of heterogeneous uptake of butanol and decanol on liquid H2SO4 in the range of 62-84 wt % and between 273 and 296 K. Both alcohols exhibit two distinct types of uptake behaviors (partially irreversible vs totally irreversible uptake), depending on the acid concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 34 publications
(83 reference statements)
3
34
1
2
Order By: Relevance
“…However, it is likely that H 2 SO 4 will have a much larger effect on processing of soot aerosols than organics, and condensation of H 2 SO 4 largely determines the aerosol hygroscopicity. Also, H 2 SO 4 condensed on aerosol particles may promote heterogeneous reactions of carbonyls and alcohols (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is likely that H 2 SO 4 will have a much larger effect on processing of soot aerosols than organics, and condensation of H 2 SO 4 largely determines the aerosol hygroscopicity. Also, H 2 SO 4 condensed on aerosol particles may promote heterogeneous reactions of carbonyls and alcohols (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…Garland et al (2006) also demonstrated that reactions of a high concentration of hexanal vapor (0.01 atm) with highly concentrated SA seed particles produce aerosols with up to 88 wt% of organics. Other groups have also shown that enhanced uptake into acidic particles occurs to commonly found VOCs that possess reactive functional groups (susceptible to proton addition), such as olefins (Limbeck et al 2003;Liggio et al 2007;Liggio and Li 2008), hydroxyls (Levitt et al 2006;Noziere et al 2006), epoxides (Surratt et al 2008;Minerath and Elrod 2009), and alkylamines (Wang et al 2010). It is proposed that the acidic medium in the particle phase acts as a catalyst (Jang et al 2002(Jang et al , 2004Liggio and Li 2006a) in particle-phase reactions of carbonyls, forming high-molecular-weight products that tend to stay in the particle phase.…”
Section: Introductionmentioning
confidence: 99%
“…Field measurements indicated that pinonic acids represent an important constituent of nanosized particles over forests (9). Also, oxygenated organic species, which are formed from oxidation of biogenic hydrocarbons (10)(11)(12), may engage in heterogeneous reactions to lead to aerosol growth (13)(14)(15).…”
mentioning
confidence: 99%